Strategies for Prevention and Management of Student Violence in Kristen Calvin Middle School Central Jakarta - Sutomo, Sugiarto; Sarkadi, Sarkadi; Mao, Lixiang (International Education Trend Issues, 2023)
School violence not only affects the physical health and safety of young people, but also their mental health, social relationships and academic performance. In addition to this, student violence in middle school has different degrees of impact on the perpetrators and those affected by the violence. This paper provides an in-depth analysis of the characteristics and manifestations of violent behavior among middle school students, and studies the related factors that influence violent behavior among middle school students. It explores the causes of school violence among middle school students from four perspectives: school, family, society, and the students themselves, and discusses the prevention and management strategies through interviews and literature research with Kristen Calvin Middle School as the research subject.